2017
DOI: 10.1124/jpet.116.238113
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Epoxide Hydrolase Pharmacological Inhibition Decreases Alveolar Bone Loss by Modulating Host Inflammatory Response, RANK-Related Signaling, Endoplasmic Reticulum Stress, and Apoptosis

Abstract: Epoxyeicosatrienoic acids (EETs), metabolites of arachidonic acid derived from the cytochrome P450 enzymes, are mainly metabolized by soluble epoxide hydrolase (sEH) to their corresponding diols. EETs but not their diols, have anti-inflammatory properties, and inhibition of sEH might provide protective effects against inflammatory bone loss. Thus, in the present study, we tested the selective sEH inhibitor, 1-trifluoromethoxyphenyl-3-(1-propionylpiperidin-4-yl) urea (TPPU), in a mouse model of periodontitis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 47 publications
(57 reference statements)
1
23
0
Order By: Relevance
“…In these animals, the chief osteoclastogenic molecules RANK/RANKL/OPG and the chemokine MCP-1 were downregulated and downstream inflammatory JNK and p38 kinase signaling was abated. In addition, this study demonstrated that ER Stress was upregulated with periodontal disease but was blocked by both sEHI administration and in the sEH knockout mice (Trindade da Silva, et al, 2017). Thus, given the role of sEHI and EpFA action against inflammation combined with the effects on other bone loss conditions, sEH inhibition may be a useful strategy to combat periodontitis.…”
Section: Seh As a Target For Inflammatory Diseasesmentioning
confidence: 84%
“…In these animals, the chief osteoclastogenic molecules RANK/RANKL/OPG and the chemokine MCP-1 were downregulated and downstream inflammatory JNK and p38 kinase signaling was abated. In addition, this study demonstrated that ER Stress was upregulated with periodontal disease but was blocked by both sEHI administration and in the sEH knockout mice (Trindade da Silva, et al, 2017). Thus, given the role of sEHI and EpFA action against inflammation combined with the effects on other bone loss conditions, sEH inhibition may be a useful strategy to combat periodontitis.…”
Section: Seh As a Target For Inflammatory Diseasesmentioning
confidence: 84%
“…These included lower DHETs but greater decreases in EETs, higher LTC 4 (activates NOX4 and induces ROS production) ( 40 ) with a corresponding decrease in its precursor LTE 4 (inflammatory through GPR99) ( 41 ), and detection of LTB 4 (potent chemoattractant and induces ROS) in the NOD-WT, relative to NOD-HET. The EETs are generated via CYP-catalyzed metabolism of arachidonic acid and have antiinflammatory properties ( 42 ). However, they can be converted by soluble epoxide hydrolase (sEH1) to DHETs, which are proinflammatory, and the present findings suggest that sEH1 is induced in the NOD, causing a decrease in the EET/DHET ratio.…”
Section: Discussionmentioning
confidence: 99%
“…As these inflammatory pathologies were examined unexpected and usually beneficial effects were observed. For example, sEHI not only reduce periodontal inflammation but also enhanced the regrowth of bone through alteration of the RANK - RANKL system [38]. The reduction of inflammation was observed in multiple models of intestinal, renal, pancreatic, brain and even cardiac inflammation, so it was not a surprise that they reduced atrial fibrillation and fibrosis that lead to cardiac hypertrophy [39].…”
Section: The Enigma Of Broad Efficacymentioning
confidence: 99%